2019
DOI: 10.6018/eglobal.18.2.313421
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Risk of Suffering Eating Disorders in young student university of Extremadura (Spain)

Abstract: Los Trastornos de la Alimentación (TA), la Anorexia Nerviosa (AN), Bulimia nerviosa (BN) y trastorno por atracón son trastornos de gran preocupación en el mundo occidental. Sus tendencias crecientes han llevado a los investigadores a tratar de explicar los factores implicados, sus causas y sus efectos, como una forma de contribuir a los esfuerzos para detener las tendencias de crecimiento.Nuestro proyecto de investigación se centra en el estudio del riesgo de padecer TA entre una muestra de 600 estudiantes de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In terms of the specific issues relating to BEDs, there is a behavioural pattern in the practice of weight-loss diets which is nearly twice as frequent in girls. These results coincide with other studies carried out on the same line of research [12,18,57]. For the purposes of designing help programs, it is important to take into account the reasons why there are differentiated behavioural patterns in boys and girls, since girls tend to think their weight is adequate to a lesser extent and the distorted perception of their weight is rarely associated with the need to put on weight, but weight loss; boys, on the other hand, feel the opposite way.…”
Section: Discussionsupporting
confidence: 93%
“…In terms of the specific issues relating to BEDs, there is a behavioural pattern in the practice of weight-loss diets which is nearly twice as frequent in girls. These results coincide with other studies carried out on the same line of research [12,18,57]. For the purposes of designing help programs, it is important to take into account the reasons why there are differentiated behavioural patterns in boys and girls, since girls tend to think their weight is adequate to a lesser extent and the distorted perception of their weight is rarely associated with the need to put on weight, but weight loss; boys, on the other hand, feel the opposite way.…”
Section: Discussionsupporting
confidence: 93%
“…Sample Size N = 804. ED Measure: SCOFF %Female = 50.4%, Age = 21.2 years, BMI = 22.2 kg/m 2 8 15 Benítez (2019) [ 91 ] Spain Cross-sectional design. Sample Size N = 600.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the aforementioned issues, the analysis of the studies included in this systematic review also revealed a clear predominance of quantitative methods in research on interventions focusing on the body image of university students. This preference indicates an emphasis on collecting numerical data and statistical analysis to investigate various aspects related to body image (e.g., Alves et al, 2017 ; Benitez et al, 2019 ). The quantitative approach allows for the objective measurement of phenomena and the establishment of relationships between variables, contributing to an understanding of the effects of interventions.…”
Section: Discussionmentioning
confidence: 99%